Sex Rewarded, Sex Punished A Study of the Status "Female Slave" in Early Jewish Law - Kriger, Diane (Academic Studies Press, 2008)
A masterful intersection of Bible studies, gender studies, and rabbinic law, Diane Kriger explores the laws pertaining to female slaves in Jewish law. Comparing biblical strictures with later rabbinic interpretations as well as contemporary Greco-Roman and Babylonian codes of law, Kriger establishes a framework whereby a woman's sexual identity also indicates her legal status. With sensitivity to the nuances in both ancient laws and ancient languages, Kriger adds greatly to our understanding of gender, slave status, and the matrilineal principle of descent in the ancient Near East.